Assessment processes and characteristics of pineapple leaf fiber woven fabric (Ananas comosus (L.) Merr.) And ambon banana stem midrib (Musa paradisiaca var. sapientum(L.) Kunt.) - Asri Widyasanti; Sita Halimatus Sa’diyah; Ahmad Thoriq (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2020)
Pineapple leaves and banana stem midribs are agricultural wastes that can be used as natural fibers and processed into fabric. The fabric processed by the woven method. The aims of this research were to analyze the stages of the production process of making woven fabric from pineapple leaf fibers and Ambon banana stem midribs and to analyze the characteristics of fabrics from pineapple leaf fibers and Ambon banana stem midribs. The method used was the experiment method. The process of made woven fabric was used handloom. The result of this research that have the best woven fabric was fabric from pineapple leaf fibers with the L* 64.33; a* 0.75; b* 15.83; H 87.26; tensile strength 53.34 kgf (weft); 23.95 kgf (warp); elongation value 10.77% (weft); 56.27% (warp); tear strength 28.42 kgf (weft); 3.73 kgf (warp); air permeability 133.80 cm3/cm2/s. The value of tensile strength and tear strength was in accordance with Indonesian National Standard 08-0056-2006 woven fabric quality requirements for suit. The use of fabric from nature fibers suggested for raw material of craft.